Perang Narasi Asimetris dalam Konflik Iran–Amerika Serikat Analisis Komunikasi Politik dan Propaganda Daring - Edy Junaedy Syaf; Irwanto Hamid; Endang Sari (Universitas Muhammadiyah Sorong, 2026)
Social media, particularly platforms like X and Truth Social, has emerged as a strategic arena in contemporary international conflicts, enabling state actors to produce and contest political meaning beyond conventional diplomatic and military channels. This article examines digital narrative warfare in the Iran–United States conflict from June 2025 to April 2026 by analyzing the online political communication of U.S. President Donald J. Trump alongside Iran’s responses through official embassy accounts. Employing critical discourse analysis, the study identifies a marked asymmetry in communication strategies: Trump constructs a narrative of dominance through personalistic, hyperbolic, and spectacular rhetoric, whereas Iran responds with irony, linguistic minimalism, and satire as a form of digital counter-propaganda. The article argues that these practices represent a manifestation of ironic counter-propaganda within post-material-violence narrative warfare, wherein conflict is sustained through meta-narrative delegitimization rather than direct counter-framing. Theoretically, this research contributes to the conceptualization of second-order narrative delegitimization and advances the understanding of digital diplomacy as an instrument of symbolic power in contemporary international politics.